Quaternary Prevention: Can and Should Damage Caused by Health Activity Be Prevented? - Kopitowski, Karin Silvana (Revista del Hospital Italiano de Buenos Aires, 2013)
Quaternary prevention is the group of activities that are carried out in order to prevent, diminish and/or alleviate damage caused by sanitary activities. Sanitary activities produce not only benefits but also damage. Damage is a factor of major importance to consider in case of prevention, since the patient to be treated is healthy. Damage caused due to prevention may include overdiagnosis, false positive results and diagnostic cascades. As all medical interventions may result in damage, each medical action, each diagnostic study, must be performed only if benefits exceed damages. It is necessary to provide medical care that has proved to improve health, and to interrupt care when the result is dangerous or useless. In addition, it is necessary to give the corresponding and suitable intervention if it is worthwhile. Frequently, the best prescription is to discontinue unnecessary medication, educate and observe the patient, and wait for some time